Analisis Kadar Klorida Air Sumur Bor Sekitar Tempat Pembuangan Akhir (TPA) II Musi II Palembang dengan Metode Titrasi Argentometri - Huljani, Mifta; Rahma, Nur (ALKIMIA, 2018)
The community around Tempat Pembuangan Akhir (TPA) II Musi II Kelurahan Karya Jaya still relying on borehole water to fulfill their daily needs. The existence of TPA around these community environments can have a negative impact, including an indication of contamination of borehole water. One of the water pollution that is suspected to occur due to contamination of leachate from TPA is over chloride level in borehole water. The present work aimed at determining chloride level in borehole water in the area around Musi II TPA II Musi II Kelurahan Karya Jaya using Mohr argentometry titration method. The results showed chloride level in borehole water in the area around Musi II TPA II Musi II Kelurahan Karya Jaya is 301.75 mg/L. Based on PerMenKes RI No.492/MENKES/SK/VI/2010 and PerMenKes RI No.416/MENKES/ PER/IX/1990, the maximum level of chloride for drinking water is 250 mg/L, while for clean water is 600 mg/L, so that it can be concluded that borehole water in the area around Musi II TPA II Musi II Kelurahan Karya Jaya can’t be used for primary needs, for example drinking and cooking needs, but borehole water can still be used for secondary needs such as bathing and washing.